Evaluation of Patients with Microangiopathic Hemolytic Anemia and Thrombocytopenia - George, James N.; Charania, Roseleen S. (Seminars in Thrombosis and Hemostasis, 2013)
When a patient presents with unexpected microangiopathic hemolytic anemia and thrombocytopenia, the diagnosis of thrombotic thrombocytopenic purpura (TTP) is often considered. However, many different disorders, including many different systemic infections and malignancies, can cause thrombotic microangiopathy (TMA), with the clinical features of microangiopathic hemolytic anemia and thrombocytopenia. Other etiologies include severe hypertension, preeclampsia, systemic lupus erythematosus, adverse drug reactions, allogeneic hematopoietic stem cell transplantation, and abnormalities of complement regulation. This article focuses on distinguishing TTP from other etiologies of microangiopathic hemolytic anemia and thrombocytopenia, because consideration of the diagnosis of TTP requires an urgent decision for the initiation of plasma exchange treatment. Awareness of the many etiologies of TMA is essential for the appropriate evaluation of patients presenting with microangiopathic hemolytic anemia and thrombocytopenia and the appropriate diagnosis of TTP.
Keywords: microangiopathic hemolytic anemia; thrombotic thrombocytopenic purpura; thrombotic microangiopathy